3
$\begingroup$

What is the generating function of $f_{m,n}$?

$ f_{m,n} = \begin{cases} 0 , & \text{if $m<0 $ or $ n<0$ }; \\ f_{n,m} , & \text{ if $n<m$}; \\ 1, & \text{ if $0=m$ and $ n\in\{0,1\} $}; \\ f_{0 ,n-1}+ f_{1,n-1}, & \text{ if $0=m$ and $ n>1 $}; \\ f_{m-1 ,n}+ f_{m ,n-1}+ f_{m-1,n-1}, & \text{ if $0<m\in \{n,n-1\} $}; \\ f_{m-1 ,n}+ f_{ m ,n-1}+ f_{m-1,n-1} + f_{m+1,n-1},& \text{ if $0<m<n-1$}. \end{cases} $

$\endgroup$
2
  • 1
    $\begingroup$ Will it yield taking partial derivatives in the two variables sequence to construct the generating function. Here is an example. math.stackexchange.com/questions/686102/… $\endgroup$ Jul 23, 2021 at 18:40
  • 2
    $\begingroup$ It might make sense to restrict to $0\le m\le n$, define boundary functions (for $n=0$, $m=n$, and $m=n-1$), and use the kernel method. $\endgroup$ Jul 24, 2021 at 7:26

1 Answer 1

2
+25
$\begingroup$

Consider the following generating function: $$F(x,y) := \sum_{n=0}^\infty \sum_{m=0}^n f_{m,n} x^n y^m$$ and its diagonal $$D(z) := \sum_{n=0}^\infty f_{n,n} z^n.$$ Then the recurrence implies the following functional equation: $$2(1-x-y-xy)F(x,y) - 2x\frac{F(x,y)-F(x,0)}y = 1 + (1-xy-2y)D(xy).$$ I'm not yet sure if it can be solved explicitly.


It's also worth to mention a couple of boundary properties for $F(x,y)$: $$[y^1]\ F(x,y) = \left.\frac{F(x,y)-F(x,0)}y\right|_{y=0} = \frac{(1-x)F(x,0)-1}x$$ and $$\sum_{n=1}^\infty f_{n-1,n} z^n = \frac{(1-z)D(z)-1}2.$$


ADDED. Introducing another generating function: $$G(x,y) := F(x,\frac{y}{x}) = \sum_{n=0}^\infty \sum_{m=0}^n f_{m,n} x^{n-m} y^m$$ we get a self-contained functional equation: $$2(y-xy-y^2-xy^2-x) G(x,xy) = y + (y-2y^2-xy^2) G(0,xy) – 2x G(x,0).$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.